KUALITAS DNA HASIL PURIFIKASI DARI SOSIS SAPI SEBAGAI BAHAN AUTENTIKASI HALAL BERBASIS MARKER GENETIK - Nurul Purnomo; Dhian Ramadhanty; Musdalifa Mansur; Maghfira Nur; Muhammad Ihsan A. Dagong (Jurnal Ilmu dan Teknologi Peternakan, 2021)
This study aims to determine the effect of the preparation method and the number of samples on the quality of purified DNA from beef sausage. The study was conducted using a Randomized Block Design. The main factor is the sample preparation method which consists of P1: fresh sample; P2: oven-dried sample; and P3: Freeze-drying dry samples. Each treatment consisted of 4 groups, namely K1: sample weight 25 mg; K2: sample weight 50 mg; K3: sample weight 75 mg; and K4: sample weight 100 mg. Each treatment group was repeated 2 times so that the total sample was 24. The results showed that DNA purification using different preparation methods and sample weights was successfully carried out, as seen from the presence of DNA bands visualized on agarose gel with EtBr staining. The average DNA quality of the P1, P2, and P3 preparation methods were 1.60±0.90 ng/μl, 2.63±0.99 ng/μl, and 2.94 ±0.89, ng/μl respectively, with DNA purity 1.023 ±0.165, 0.937±0.148, and 1.014±0.163. The average DNA quality at K1, K2, K3, and K4 obtained DNA concentrations of 3.03±1.64 ng/μl, 3.15±0.74 ng/μl, 2.28± 1.66 ng/μl, and 2.54±1.50 ng/μl with a purity of 1.059±0.142, 0.981±0.130, 0.908±0.061, and 1.061± 0.215. The average total concentration of purified DNA from beef sausage was 2.75±1.28 ng/μl with a purity of 0.991±0.149. The results of variance showed that the treatment did not affect the concentration and purity of purified DNA from beef sausage. This study concludes that DNA purification from beef sausage can be carried out, but the preparation method and number of samples do not affect the quality and quantity of DNA.